Pengaruh Pemanfaatan Smart Office Terhadap Keberlangsungan Operasional Perusahaan di Jakarta (Studi Kasus Tenant PT Menara Properti Indonesia Tahun 2021) - Mayang Sari; Achmad Sulistyono (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
The purpose of this study is to determine the use of Smart Office which consists of two indicators, namely Virtual Office and Serviced Office on the Company's Operational Sustainability which consists of several indicators, including desks, chairs, and private offices; internet connection, and electricity; free printing; free meeting rooms; full pantry; receptionist; cleaning services; and the domicile of the company at the tenants registered with PT Menara Properti Indonesia. This study uses a survey method conducted on all tenants registered at PT Menara Properti Indonesia, both users of Virtual Office and Serviced Office services. The results of this study indicate that there is an influence between the use of smart offices and the company's operational sustainability at the tenants of PT Menara Properti Indonesia.